Delphi technique in plastic surgery research priority setting: a systematic review - Angus RJ Barber; Guy HM Stanley; Sarah Li-Ling Goh; Cheryl Hamill; Michael Findlay (Australasian Journal of Plastic Surgery)
**Background:** Delphi research priority setting exercises in plastic and reconstructive surgery aim to encourage future research in areas that align with clinical needs. This can guide the allocation of research funding and further the knowledge base of the speciality. This systematic review evaluates the content and quality of existing Delphi research priority setting studies in plastic and reconstructive surgery, to inform future studies. **Method:** A predefined protocol and PRISMA guidelines were followed. The search was performed by a research librarian. Screening and data extraction was performed in duplicate with a third reviewer arbitrating. Primary outcomes included the number of studies and subject areas. Secondary outcomes were the methods and results (including types of stakeholders, uncertainties, numbers of stakeholders, journal impact factor, implementation plans and dissemination plans). The risk of bias was assessed using four domains of quality. Data underwent synthesis with descriptive statistics. **Results:** Seven articles were included in the review, covering breast reconstruction, craniomaxillofacial, burns, aesthetics, skin and soft tissue, and general plastics. Studies had national or international scope, used either Delphi or modified Delphi methodology, and had a variable number of rounds. Four included studies had funding, and implementation plans were absent in four included studies. **Discussion and conclusion:** Included studies had a variable methodology, making a direct comparison between studies difficult. Six of the seven included studies had a high or moderate risk of bias, and implementation plans for studies were variable or absent. The review highlights the need for future Delphi research priority setting exercises to have a more standardised method and adhere to quality criteria.